Efeito do espectro de gotas e idade de trifólios sobre a taxa de absorção de fungicidas em soja - Lenz, Giuvan (2010)
Currently, the Asian soybean rust is the main disease of this crop in Brazil and chemical control, so far, is the only effective measure to reduce losses. The development of control strategies for this disease requires knowledge of how performance of products applied, application technology used as well as their interaction with plants. This work aimed to quantify the effect of large, medium and fine droplet spectra and its interaction with the fungicide absorption rate and leaflets age through indirect measure expressed by the control of Phakopsora pachyrhizi in soybean. The experiment was performed twice and that was first installed in January 2010 and repeated in March this year. The experimental design was composed by completely randomized design with four replications in a factorial (3x3x5x4), which factors were composed of: three spectra drops (large, medium and fine); factor 02: evaluation in different positions of the plant (1º, 3º and 5 leaflets), factor 03: four time periods between the fungicide application and simulated rain (0, 30, 60 and 120 ) and a control with no rain and still a factor 04: control without fungicide applying, Azoxystrobin+Cyproconazole (60+24 g a.i. ha-1) + Nimbus 0.6 L.ha-1, Azoxystrobin (50 g a.i. ha-1) + Nimbus 0.6 L.ha-1 and Cyproconazole (30 g a.i. ha-1). We evaluated the density of droplets per square centimeter, volume median diameter, number median diameter and relative amplitude, disease severity and area under the disease progress curve. It was found that drops with smaller volume median diameter have higher fungicides absorption rates because they provide a greater number of drops per square centimeter and hence larger contact area specific product / plant. Newer leaflets provide more quickly fungicides absorption and therefore, provide a longer delay in disease development. The use of Azoxystrobin + Cyproconazole provided the greatest number of days until the first pustule preview and smaller area under the disease progress curve. The influence of rain has highly dependent on the interval between application of the products and its occurrence, the product applied and tissues age considered.